Pemerolehan Informasi Pada Alkitab Berbahasa Indonesia Dengan Bm25f Dan Query Expansion Wordnet Bahasa - Amelia Kosasih; Putra Pandu Adika; Yuita Arum Sari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
As an Indonesian who had a religion, holy book is something important that cannot be separated from worship. Thanks to technological advances, it is increasingly easier to find information, such as in reading holy books. Time becomes so much important so we are always required to be fast even in obtaining information. However, this is not matched by the content of the holy book which is not just few. Therefore, we need an information retrieval system that can generate information that user wants precisely and quickly. BM25F method used for ranking documents because it considers the document structure by giving weight to each field. In addition, the query expansion technique using a thesaurus in the form of WordNet is also applied to solve the problem of human mistakes or ambiguities of the queries entered by the user. Tests conducted on the boost value on the BM25F get the best results at title boost 5 and content boost 1 with an average precision@k value of 0.95 at k=5 and an average r-precision value of 0.84. Testing without using query expansion produces an average precision@k value of 0.896 and an average r-precision value of 0.956, while testing using query expansion produces an average value of precision@k of 0.884 and an average r-precision value of 0.936.